Transcriptional gene expression profiles of HGF/SF-met signaling pathway in colorectal carcinoma - Li, Xue-Nong (World J Gastroenterol, 2003)
AIM: To explore the transcriptional gene expression profiles of HGF/SF-met signaling pathway in colorectal carcinoma to understand mechanisms of the signaling pathway at so gene level. METHODS: Total RNA was isolated from human colorectal carcinoma cell line LoVo treated with HGF/SF (80 ng/L) for 48 h. Fluorescent probes were prepared from RNA labeled with cy3-dUTP for the control groups and with cy5-dUTP for the HGF/SF-treated groups through reverse-transcription. The probes were mixed and hybridized on the microarray at 60 °C for 15-20 h, then the microarray was scanned by laser scanner (GenePix 4000B). The intensity of each spot and ratios of Cy5/Cy3 were analyzed and finally the differentially expressed genes were selected by GenePix Pro 3.0 software. 6 differential expression genes (3 up-regulated genes and 3 down-regulated genes) were selected randomly and analyzed by β-actin semi-quantitative RT-PCR. RESULTS: The fluorescent intensities of built-in negative control spots were less than 200, and the fluorescent intensities of positive control spots were more than 5000. Of the 4004 human genes analyzed by microarray, 129 genes (holding 3.22% of the investigated genes) revealed differential expression in HGF/SF-treated groups compared with the control groups, of which 61 genes were up-regulated (holding 1.52% of the investigated genes) and 68 genes were down-regulated (holding 1.70% of the investigated genes), which supplied abundant information about target genes of HGF/SF-met signaling. CONCLUSION: HGF/SF-met signaling may up-regulate oncogenes, signal transduction genes, apoptosis-related genes, metastasis related genes, and down-regulate a number of genes. The complexity of HGF/SF-met signaling to control the gene expression is revealed as a whole by the gene chip technology.